Evaluation of Two Commercially Available Cannabidiol Formulations for Use in Electronic Cigarettes - Peace, Michelle R.; Butler, Karen E.; Wolf, Carl E.; Poklis, Justin L.; Poklis, Alphonse (Frontiers in Pharmacology, 2016)
With 24 states and the District of Columbia with laws legalizing marijuana in some form, suppliers of legal marijuana have developed Cannabis sativa products for use in electronic cigarettes. Personal battery powered vaporizers or electronic cigarettes were developed to deliver a nicotine vapor such that smokers could simulate smoking tobacco without the inherent pathology of inhaled tobacco smoke. The liquid formulations used in these devices are comprised of an active ingredient such as nicotine mixed with glycerin and/or propylene glycol and flavorings. A significant active ingredient of Cannabis sativa, cannabidiol, has been purported to have anti-convulsant, anti-nociceptive, and anti-psychotic properties. These properties have potential medical therapies such as intervention of addictive behaviors, treatments for epilepsy, management of pain for cancer patients, and treatments for schizophrenia. However, cannabidiol extracted from Cannabis sativa remains a DEA Schedule I drug since it has not been approved by the FDA for medical purposes. Two commercially available e-cigarette liquid formulations reported to contain 3.3 mg/mL of cannabidiol as the active ingredient were evaluated. These products are not regulated by the Food and Drug Administration in manufacturing or in labeling of the products and were found to contain 6.5 mg/mL and 7.6 mg/mL of cannabidiol in propylene glycol with a variety of flavoring agents. Presently, while labeled as to content, the quality control of manufacturers and the relative safety of these products is uncertain.